2019
DOI: 10.1007/s10096-018-03451-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-operative antimicrobial treatment on microbiological findings from endocardial specimens in infective endocarditis

Abstract: Treatment of infective endocarditis (IE) should be initiated promptly. This might hamper the chances to identify the causative organism in blood cultures. Microbiological sampling of infected valve in patients undergoing surgery might identify the causative organism. The impact of pre-operative antimicrobial treatment on the yield of valve samples is not known. This study evaluated the impact of the duration of the pre-operative antibiotic treatment on valve culture and 16S rRNA PCR findings from resected endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
4
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
4
11
4
3
Order By: Relevance
“…In addition, valve PCR can substantiate earlier results of blood culture positive infective endocarditises [ 13 ]. Halavaara et al describe 62% of surgical patients with such confirmed results [ 21 ], while we found concordant findings of blood cultures and valve PCRs in 63/146 (43%) of surgical infective endocarditises. The majority of cases with different microorganisms detected by blood culture and valve PCR in our study occurred when skin commensals appeared in blood culture but were refuted by valve PCR, which identified a typical pathogen on the valve (Table S3); for these patients valve PCR provided a diagnostic benefit.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, valve PCR can substantiate earlier results of blood culture positive infective endocarditises [ 13 ]. Halavaara et al describe 62% of surgical patients with such confirmed results [ 21 ], while we found concordant findings of blood cultures and valve PCRs in 63/146 (43%) of surgical infective endocarditises. The majority of cases with different microorganisms detected by blood culture and valve PCR in our study occurred when skin commensals appeared in blood culture but were refuted by valve PCR, which identified a typical pathogen on the valve (Table S3); for these patients valve PCR provided a diagnostic benefit.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also confirm observations by Fournier et al and Goldenberg et al that blood culture-negative endocarditises benefit from detection through valve PCR and that blood culture positive infective endocarditises can be substantiated by concordant valve PCRs [ 8 , 13 ]. Valve PCR was also significantly more successful in pathogen identification than valve culture, a tendency that has already been described [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In total, 103 blood culture bottles (BacT/Alert, bioMérieux, France), one bottle per patient, confirmed to contain either Gram-negative bacteria, Gram-positive rods, Gram-positive diplococci, cocci in chains, yeast, or polymicrobial growth by Gram-staining and evaluation by a clinical microbiologist, were analyzed between November 2020 and January 2021 with the FilmArray BCID2 assay and routine reference methods. Routine methods included subculture from the signal-positive bottle on rich universal agars, such as blood, chocolate, and fastidious anaerobe agar plates with incubation at 35 °C in normal atmosphere as well as in elevated CO 2 and in anaerobic conditions for 24 to 48 h. Microbial isolates were identified by Vitek MS (bioMérieux, France) and in case of unclear result confirmed by 16S rDNA sequencing [21]. Antimicrobial susceptibilities were determined using disc (Oxoid, UK) and/or MIC-gradient (M.I.C.E, Oxoid, Basingstoke, UK, and ETest, bioMérieux, France) diffusion tests on Mueller-Hinton agar (BD, USA) at 35 °C for 24 to 48 h. Phenotypic susceptibility profile for each isolate was interpreted according to the EUCAST standard [22].…”
Section: Clinical Samplesmentioning
confidence: 99%